Among friends: a qualitative exploration of the role of peers in young people's alcohol use using Bourdieu's concepts of habitus, field and capital. Issue 1 (30th August 2016) - MacArthur, Georgie J.; Jacob, Nina; Pound, Pandora; Hickman, Matthew; Campbell, Rona
Abstract: Drinking is viewed by young people as a predominantly social activity which provides an opportunity for entertainment and bonding with friends. Using Bourdieu's concepts of habitus, field and capital, this article explores young people's attitudes and beliefs around alcohol use, influences on behaviour, and the role of peers, with a view to informing the development of preventive interventions. Semi‐structured interviews were conducted with 28 young people aged 18–20 in the south west of England. We describe how friends were integral in drinking experiences, and drinking with friends was equated with fun and enjoyment. In this way, the desire for social and symbolic capital appeared to be a key motivator for adolescent drinking. Critically, however, wider cultural norms played the predominant role in shaping behaviour, via the internalisation of widely accepted practice and the subsequent externalisation of norms through the habitus. Applying Bourdieu's theory suggests that population‐level interventions that regulate alcohol consumption, and thus disrupt the field, are likely to facilitate behaviour change among young people by driving a response in habitus.